Comparison of Three Embankment Reinforcement on Soft Soil, A Case Study of Calang – Simpang Peut Road Section - Doni Mardian; Indrasurya B Mochtar; Dedy Mandarsyah (Journal of Infrastructure & Facility Asset Management, 2024)
One of the road damages caused by problematic soil is found on the Calang - Simpang Peut Road Section. Soil testing data shows that soft soil exists at a depth of zero meters, up to five meters. The damage is being repaired using a Modified Cakar Ayam (CAM) system. The CAM system is built on a road embankment. Using the CAM on the top of the road embankment has a settlement problem that will cause non-uniform settlement. This study reviews three alternatives that have been proven effective and efficient in fixing road embankment failures on problematic soils. These alternatives are geosynthetic reinforcement, geosynthetic reinforcement with prefabricated vertical drain (PVD), and encapsulated stone columns. This research will analyze the three alternatives based on their efficiency and effectiveness in treating the damage. The results of the calculation analysis show that the geosynthetic-reinforced embankment is the most effective alternative design. The alternative can also reduce the execution time by 42% and cost by 43% compared to the CAM system. However, a subgrade improvement alternative with encapsulated stone columns increases the execution time by 20% and cost by 25% compared to the CAM system, and using a PVD alternative is not recommended to repair the road embankment on this road section.